A NEW SPECIES OF DIPLODISCUS TURCZ. (TILIACEAE), RELATED TO BROWNLOWIA ROXB. - Kostermans, AJGH (REINWARDTIA, 1992)
Diplodiscus longipetiolatus Kosterm. is described based on a specimen collected in East Kalimantan.